India, Germany and Europe. A Spatial Perspective at SDG 4 on Quality Education. - Binot, Regine; Debnath, Tania; Kar, Biswajit; Kundu, Debolina; Milbert, Antonia; Mishra, Rakesh; Müller, André; Schmidt-Seiwert, Volker (My University, 2020)
Responding to crucial challenges in urban and rural development the United Nations decided on the New Urban Agenda and on the 2030 Agenda and the Sustainable Development Goals (SDGs). This publication checks the progress made in implementing the New Urban Agenda against the SDGs and vice versa. In order to understand the spatial patterns, a national and supranational spatial perspective is taken on some of the SDGs. Given the significance of quality education, SDG 4 thus covers: All gender early school leavers with low and high educational qualification and students; Female early school leavers with low and high educational qualification and female students; Scholar exclusion.
Keywords: Nachhaltige Entwicklung; Bildungswesen; Bildungsangebot; Räumliche Disparität; Schulversorgung; Hochschulstudium; Stadt-Land-Vergleich; Internationaler Vergleich; Sozialindikator; Sustainable Development Goals; Agenda 2030 für nachhaltige Entwicklung; New Urban Agenda